The Effect of Giving NPK and Biochar from Palm Oil Fronds on Palm Oil Main Nursery Seedlings: NPK and Biochar from Palm Oil Fronds on Palm Oil Main Nursery Seedlings - Kristian Tinduh, Yulio; Fitriana Dyah Ratnasari, Ika; Malik, Amalia; Fikriyadi, Ahmad; Aprilianto, Devin (TROPICAL WETLAND JOURNAL, 2024)
This study aims to determine the effect of NPK and biochar made from oil palm fronds on the growth of palm oil seedlings at the main nursery stage using 4-month-old palm oil seedling samples. The experimental design used was a Randomized Block Design with two treatment factors with three replications. The first treatment factor was the administration of NPK 15-15-6-4 with a dose of 0.1 grams, 2 grams/polybag and the second factor was the administration of oil palm frond biochar with a dose of 0, 2.5 grams, and 5 grams. The results of research to observe the height parameters of palm oil seedlings in the main nursery, the best plant height was shown in B1N2 seedlings with a total height of 33.2 cm in the 7th week with a dose of 2.5 grams of B1N2 palm oil frond biochar and 2 grams of NPK. The highest number of fronds was found in B2N2 main nursery palm oil seeds with a total of 6 fronds, namely at a dose of 5 grams of biochar and 2 grams of NPK. The best enlargement of palm oil stump diameter was found in main nursery B0N2 palm oil seeds with an average stump diameter of 120.9 mm. The administration of NPK and biochar from palm oil fronds had a good effect on the height of palm oil seedlings, the number of palm oil fronds and good tuber enlargement.